A resposta do sistema brasileiro de inovaç\~ao em saúde à Covid-19: As políticas públicas e o papel da Fiocruz e do Butantan - Ana Lúcia Tatsch; Marisa dos Reis A. Botelho; Priscila Koeller (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This paper analyzed the role of the two official laboratories - Oswaldo Cruz Foundation (Fundaç\~ao Oswaldo Cruz - Fiocruz) and Butantan - in facing the covid-19 pandemic in Brazil, based on the analysis of the process of building their productive and innovative capabilities and the public policies that supported them. The methodological procedures involved literature review, documentary research, and data collection. It was found that, from the identification of a mission (to ensure sufficiency in the supply of immunizers) and from policies that used mainly public procurement, a large capacity for vaccine production was developed. This, however, was not based on an endogenous innovation capacity. Fiocruz and Butantan, centennial public laboratories that provide the universal health system, whose capabilities are the result of long-term investments, were protagonists in the initiatives to face the recent health crisis. It is understood, therefore, that the State played a key role in the construction of the Brazilian Health Innovation System, as it will play it in the future in the search to overcome its weaknesses.
Keywords: I18; O32; O38; 330; covid-19; innovation policy; health policy; technology transfer; vaccine production